Small Great Things: A Novel - Jodi Picoult (2016)
As a "successful middle-class" African-American woman I was truly stunned to recognize so many aspects of my own life in Ruth. I have read every Picoult book - some twice - but never have I had my own experiences articulated so effectively by someone who isn't a person of color. I finished it yesterday morning and was rattled all day by the insights and depth of honesty revealed here. I still am, but had to take a moment to post everywhere and say THANK YOU!! Jodi, I read your acknowledgments of how you created this book, and I wish I could meet you. I am awed and will recommend this book to anyone I know: starting with my husband. Blessings to you for your courage, research and determination to see beyond what you knew, what was comfortable - and take this risk.